Analisis Karakteristik Bangkitan Perjalanan Pada Perumahan Villa Mutiara, Kota Palopo - Ruli Amsal Tikupadang (Paulus Civil Engineering Journal, 2025)
Salobulo, located in the North Wara District of Palopo City, is the site of the Villa Mutiara housing project. This housing complex is strategically located near the center of Palopo City, which also serves as a hub for government and private offices, educational facilities, shopping centers, and other businesses that stimulate demand. Primary data collection was carried out by distributing questionnaires to each family member residing in the Villa Mutiara housing complex in Palopo City. The data was analyzed using descriptive statistical methods, correlation tests, and multiple linear regression. The results obtained indicate that the factors influencing the number of trips generated in this housing complex are the number of motorcycles owned, the number of cars owned, the number of family members who work, the type of vehicle used, the time of departure and return from work, travel distance, and transportation costs.